2019
DOI: 10.1021/acs.inorgchem.9b01200
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Insights into the Selective Extraction of Americium(III) over Europium(III) with Dithioamide-Based Ligands

Abstract: Separation of trivalent actinides An­(III) from lanthanides Ln­(III) is a worldwide challenge owing to their very similar chemical behaviors. It is highly desirable to understand the nature of selectivity for the An­(III)/Ln­(III) separation with various ligands through theoretical calculations because of their radiotoxicity and experimental difficulties. In this work, we have investigated three dithioamide-based ligands and their extraction behaviors with Am­(III) and Eu­(III) ions using the scalar-relativist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 80 publications
2
46
0
Order By: Relevance
“…It is generally considered that the atom corresponding to the place where the ESP is negative is a nucleophilic site. [ 4,19 ] It is obvious from Figure 3 that the blue region is mainly concentrated around the sulfur and oxygen atoms, and the negative region of HTTDN is also mainly present in the cavity of the ligand. Moreover, the two smallest extreme points also appear here, the value of the extreme point close to the O 3 atom is −40.92 kcal mol −1 , and the value of the extreme point around the O 4 atom is −38.27 kcal mol −1 , revealing that O 3 has greater coordination affinity for uranyl than O 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally considered that the atom corresponding to the place where the ESP is negative is a nucleophilic site. [ 4,19 ] It is obvious from Figure 3 that the blue region is mainly concentrated around the sulfur and oxygen atoms, and the negative region of HTTDN is also mainly present in the cavity of the ligand. Moreover, the two smallest extreme points also appear here, the value of the extreme point close to the O 3 atom is −40.92 kcal mol −1 , and the value of the extreme point around the O 4 atom is −38.27 kcal mol −1 , revealing that O 3 has greater coordination affinity for uranyl than O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed that for pyridylpyrazole ligands, increasing the bridging skeleton was more conducive to improving the extraction and separation ability than increasing the side chain. Wang et al [ 19 ] theoretically explored the relationship between three dithioamide‐based ligands and Am(III)/Eu(III) selectivity and broadened the understanding of the separation mechanism between Am(III)/Eu(III) and dithioamide‐based ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of the ligands to attract metal atoms is often influenced by the charge on the coordinating atoms of the ligands. [14] Consequently, the charges present on the metal, oxygen and nitrogen atoms have been calculated and analysed (Figure 5 and Supporting Information Table 2 (SIT-2)). Results show that the nitrogen atoms have a lower negative charge than that of the oxygen atoms.…”
Section: Natural Population Analysismentioning
confidence: 99%
“…10a, and a depiction of selected valence MOs are shown in Figure 10b. We focused on analysis of the valence orbitals rather than the electronic excitations, because, as shown in previous studies, 87,88 such analysis is sufficient to qualitatively elucidate coordination properties.…”
Section: Iiid Electronic Structure Of Eu 3+ -Ligand Complexesmentioning
confidence: 99%